2018
DOI: 10.1177/1098612x18796672
|View full text |Cite
|
Sign up to set email alerts
|

Influence of needle gauge and venepuncture difficulty on thromboelastography in healthy cats

Abstract: Objectives The aim of this study was to evaluate the effect of two differently sized butterfly catheter needles and the effect of venepuncture difficulty on thromboelastography (TEG) results in healthy cats. Methods Twenty-four healthy cats were included. Blood samples were collected from the jugular vein by syringe aspiration via direct venepuncture with 21 G and 22 G butterfly needles. The venepuncture difficulty score was classified into four categories. The first 1.5 ml blood drawn from each subject was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…12 However, the large CV between paired samples for multiple parameters, particularly CT, suggest that the observed difference might be clinically relevant. Previous canine and feline studies using recalcified citrated samples have not identified effects of needle or catheter gauge on viscoelastic parameters, 10,13 and canine studies have not detected differences between jugular and saphenous samples. 9 The more hypercoagulable results for jugular venipuncture in the current study suggest immediate analysis of non-anticoagulated blood is more sensitive to factors such as the thicker skin overlying the jugular vein, and thus greater comparative trauma and potential for tissue factor contamination with jugular vs saphenous venipuncture.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…12 However, the large CV between paired samples for multiple parameters, particularly CT, suggest that the observed difference might be clinically relevant. Previous canine and feline studies using recalcified citrated samples have not identified effects of needle or catheter gauge on viscoelastic parameters, 10,13 and canine studies have not detected differences between jugular and saphenous samples. 9 The more hypercoagulable results for jugular venipuncture in the current study suggest immediate analysis of non-anticoagulated blood is more sensitive to factors such as the thicker skin overlying the jugular vein, and thus greater comparative trauma and potential for tissue factor contamination with jugular vs saphenous venipuncture.…”
Section: Discussionmentioning
confidence: 89%
“…Both sampling sites and needle gauges have been previously used in viscoelastic studies in cats. 10,11 Identification of statistical differences between the two sites suggest that the same site and needle gauge should be used consistently for serial monitoring or for research purposes. Our findings also suggest that different reference intervals (RIs) may be required for different venipuncture techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation